The effect of organizational culture and leadership style on job satisfaction and tutor performance - Carla Dita; Usup Riassy Christa; Meitiana Meitiana (Jurnal Inovasi Ekonomi, 2022)
This study aims to determine: 1) the effect of organizational culture on tutor performance; 2) The influence of leadership style on tutor performance; 3) the influence of organizational culture on job satisfaction; 4) the influence of leadership style on job satisfaction; 5) the effect of job satisfaction on performance tutor at Center for Community Learning Activities (PKBM) Luthfillah and Tilung Raya. This study uses a quantitative approach, and questionnaires carry out data collection techniques. The sampling technique used was saturated sampling, which amounted to 33 respondents. Respondents in this study were all PKBM tutors, Luthfillah and Tilung Raya. The data analysis method in hypothesis testing uses Partial Least Square (PLS). The results of this study indicate that organizational culture and leadership style affect job satisfaction. On the other hand, Organizational Culture has no significant effect on tutor performance. Furthermore, job satisfaction influences tutor performance.